2010
DOI: 10.1007/s00253-010-2561-z
|View full text |Cite
|
Sign up to set email alerts
|

Citric acid production from glycerol-containing waste of biodiesel industry by Yarrowia lipolytica in batch, repeated batch, and cell recycle regimes

Abstract: Yarrowia lipolytica A-101-1.22 produces high citric acid (112 g l(-1)) with a yield of 0.6 g g(-1) and a productivity of 0.71 g l(-1) h(-1) during batch cultivation in the medium with glycerol-containing waste of biodiesel industry. However, it was observed that the specific citric acid production rate, which was maximal at the beginning of the biosynthesis, gradually decreases in the late production phase and it makes continuation of the process over 100 h pointless. The cell recycle and the repeated batch re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
96
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(114 citation statements)
references
References 27 publications
13
96
0
5
Order By: Relevance
“…In general, citric acid is formed via submerged microbial fermentation on molasses using Aspergillus niger (Ali et al, 2002;Papagianni, 2007). In recent years, several investigations concerned the use of Yarrowia lipolytica in crude glycerol conversion to citric acid (Lewinson et al;Rymowicz et al, 2010;. Lewinson (2007) reported 21.6 g/L of citric acid production in batch fermentation of glycerol with 54% yield using Yarrowia lipolytica NRRL YB-423.…”
Section: Citric Acidmentioning
confidence: 99%
“…In general, citric acid is formed via submerged microbial fermentation on molasses using Aspergillus niger (Ali et al, 2002;Papagianni, 2007). In recent years, several investigations concerned the use of Yarrowia lipolytica in crude glycerol conversion to citric acid (Lewinson et al;Rymowicz et al, 2010;. Lewinson (2007) reported 21.6 g/L of citric acid production in batch fermentation of glycerol with 54% yield using Yarrowia lipolytica NRRL YB-423.…”
Section: Citric Acidmentioning
confidence: 99%
“…by-products such as raw glycerol, producing large amounts of SCO and organic acids (Papanikolaou et al, 2003;Rymowicz et al, 2010;Rywinska et al, 2009). Biochemistry of lipid production on glycerol has been investigated in this organism: glycerol passes into the microbial cell by facilitated diffusion and the conversion is carried out via phosphorylation pathway, with direct phosphorylation to G3P and subsequent dehydrogenation.…”
Section: Substrates and Raw Materialsmentioning
confidence: 99%
“…In recent years, glycerol has been successfully used as a carbon source in the production of citric acid with Y. lipolytica [6,18,19,26,27]. In the literature, it has been reported that in addition to studies in which pure glycerol is used as a substrate, there are other studies in which crude glycerol is used as a byproduct in the production of biodiesel and soap [2,3,19,22,28].…”
Section: Discussionmentioning
confidence: 99%